2008
DOI: 10.1002/adfm.200701134
|View full text |Cite
|
Sign up to set email alerts
|

MEL‐type Pure‐Silica Zeolite Nanocrystals Prepared by an Evaporation‐Assisted Two‐Stage Synthesis Method as Ultra‐Low‐k Materials

Abstract: A MEL‐type pure‐silica zeolite (PSZ), prepared by spin‐on of nanoparticle suspensions, has been shown to be a promising ultra‐low‐dielectric‐constant (k) material because of its high mechanical strength, hydrophobicity, and chemical stability. In our previous works, a two‐stage synthesis method was used to synthesize a MEL‐zeolite nanoparticle suspension, in which both nanocrystal yield and particle size of the zeolite suspension increased with increasing synthesis time. For instance, at a crystal yield of 63%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…It is most likely that these two parameters have a direct effect on the size of the voids. In that regard, Liu et al have developed an 'evaporation-assisted two-stage synthesis that apparently limits the formation of 40-80 nm zeolite nanoparticles in solution leading to low-k films with improved properties' [147]. They have reported that small MEL nanocrystals (e.g.…”
Section: Silica Zeolitesmentioning
confidence: 99%
“…It is most likely that these two parameters have a direct effect on the size of the voids. In that regard, Liu et al have developed an 'evaporation-assisted two-stage synthesis that apparently limits the formation of 40-80 nm zeolite nanoparticles in solution leading to low-k films with improved properties' [147]. They have reported that small MEL nanocrystals (e.g.…”
Section: Silica Zeolitesmentioning
confidence: 99%
“…A bottle‐neck in the application of zeolite films as low‐ k dielectrics is the presence of 40–80 nm zeolite nanoparticles composing the film, causing both large mesopores and hampering the grooving of nanofeatures. Evaporation‐assisted two‐stage synthesis of MEL‐type zeolite nanosuspensions avoiding 40–80 nm zeolite nanoparticle formation in suspension was recently proposed in this journal for the preparation of zeolite films with improved properties and with possibility to groove nanofeatures at 65 nm 1. We reproduced such zeolite films using that procedure involving well dispersed zeolite nanosuspension and characterized the porosity using ellipsometric porosimetry.…”
Section: Average Hydrodynamic Particle Diameter Measured By Dls [Nm]mentioning
confidence: 99%
“…The preparation of films by spin coating of nanocrystal suspensions of Silicalite‐1 and ‐2 type zeolites is being intensively investigated for their applicability as ultra‐low‐ k materials in nanoelectronic devices 1–4. Despite their low dielectric constant, they offer limitations related to the use of zeolite nanocrystal suspensions with particle sizes of ∼40–80 nm 1, 3e, 3f. The main drawbacks are the important surface roughness, the formation of large mesopores between individual nanocrystals, and the difficulty to groove nanofeatures.…”
Section: Average Hydrodynamic Particle Diameter Measured By Dls [Nm]mentioning
confidence: 99%
“…However, the previously reported zeolite film fabrication techniques have limitations for low‐ k applications. Two different processes have been previously used to prepare low‐ k zeolite films: in situ crystallization and spin‐on deposition of zeolite crystals. In situ crystallization allows for the fabrication of high mechanical strength zeolite films.…”
Section: Introductionmentioning
confidence: 99%